2022
DOI: 10.3390/app12063208
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Gamma Rays According to Exposure Time on Germination and Plant Growth in Wheat

Abstract: Gamma rays as a type of ionizing radiation constitute a physical mutagen that induces mutations and could be effectively used in plant breeding. To compare the effects of gamma and ionizing irradiation according to exposure time in common wheat (Keumgang, IT 213100), seeds were exposed to 60Co gamma rays at different dose rates. To evaluate the amount of free radical content, we used electron spin resonance spectroscopy. Significantly more free radicals were generated in the case of long-term compared with sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 54 publications
0
25
0
1
Order By: Relevance
“…In their study on the dose-and time-dependent effects of γ-irradiation on germination rate, plant growth, chlorophyll content, oxidative stress (OS), gene expression, and antioxidant activity changes, Hong et al [ 60 ] reported that long-term exposure to γ-rays had a significantly negative effect on the seed germination percentage. Also, they observed no differences in the final germination percentage between control and irradiated seeds.…”
Section: Discussionmentioning
confidence: 99%
“…In their study on the dose-and time-dependent effects of γ-irradiation on germination rate, plant growth, chlorophyll content, oxidative stress (OS), gene expression, and antioxidant activity changes, Hong et al [ 60 ] reported that long-term exposure to γ-rays had a significantly negative effect on the seed germination percentage. Also, they observed no differences in the final germination percentage between control and irradiated seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The use of gamma radiation on grain has been debatable. Some argue that this type of ionizing radiation can induce mutations being effectively beneficial in plant breeding [ 19 ]. Some suggests gamma radiation caused high mortality and being harmful for germination [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An adaptive response was first demonstrated using mutations in bacteria, and later the same phenomenon was identified in other objects. It is especially characteristic of physical mutagens (Holme et al, 2019;Hong et al, 2022). Although there are hypotheses about the mechanisms of this phenomenon, there is no definitive justification for this effect (Khursheed et al, 2015;Palmieri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%